Emergency Department Overcrowding in Turkey: Reasons, Facts and Solutions - Oya Durmus Cakir; Sebnem Eren Cevik; Mehtap Bulut; Ozlem Guneyses; Sule Akkose Aydin (Journal of Nepal Medical Association, 2014)
Introduction: The purpose of this study was to determine the factors affecting the long waiting times of the patients in a university hospital.